PENGEMBANGAN MEDIA PEMBELAJARAN MULTIMEDIA MODEL TUTORIAL PADA MATA PELAJARAN ANIMASI 3 DIMENSI UNTUK SISWA KELAS XII PROGRAM KEAHLIAN MULTIMEDIA DI SMK NEGERI 3 SINGARAJA - Udayana, I Nyoman (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
This research aimed at: (1) developing tutorial model as a media in multimedia learning of 3-D animation subject to the xii grade students of multimedia program in SMKNegeri 3 Singaraja, (2) knowing the students response of developing tutorial model as a media in multimedia learning of 3-D animation subject to the xii grade students ofmultimedia program in SMK Negeri 3 Singaraja. The subject of this research was 34 students of the xii grade multimedia program inSMK Negeri 3 Singaraja in the academic year 2009/2010. This research had been done as adevelopment research. The obtain data were collected through the questionnaire in order to get the students’ response on developing tutorial model as a media in multimedia learning of3-D animation subject. This data were then analyzed descriptively.The results of the analysis showed that the students’ response on developing tutorial model as a learning multimedia media in 3-D animation subject spread on some categories of77% very positive, 23% positive, 0% doubt, 0% negative, and 0% very negative. The averagestudents’ response score was 82.80 that mean that the students’ response was categorized very positive.